2023
DOI: 10.1021/acs.jpcc.3c05279
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Luminescence in Zn+2-Induced Au14 Nanocluster Aggregates

Dipankar Bain,
Aarti Devi,
Rashi
et al.

Abstract: Aggregation-induced emission (AIE) is an emerging strategy used for the creation of superstructures constructed by the selfassemblies of metal nanoclusters (NCs) to tune their photophysical properties. Here, we explored the AIE of D-penicillamine-capped Au 14 NCs by introducing Zn 2+ ions with intriguing photophysical properties. The electrostatic interaction between the carboxylate (−COO − ) groups of penicillamine ligands in the NCs with Zn 2+ ions formed large cross-linked aggregated structures evident from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…27–29 As a result, significant attention has been directed towards creating highly precise architectures and employing ligand-protected metal nanoclusters with atomic-level precision. 30–32 Metal NCs, due to their ultrasmall small sizes of nearly 2 nm with fascinating properties and atomic precision, have gained significant attention towards their applications in catalysis. 33–36 Atomically precise gold nanoclusters offer precise control over their geometric structure, electronic properties, and surface ligands, thus holding significant appeal as catalysts for electrochemical reactions due to their ultrasmall size and high surface-active sites.…”
Section: Introductionmentioning
confidence: 99%
“…27–29 As a result, significant attention has been directed towards creating highly precise architectures and employing ligand-protected metal nanoclusters with atomic-level precision. 30–32 Metal NCs, due to their ultrasmall small sizes of nearly 2 nm with fascinating properties and atomic precision, have gained significant attention towards their applications in catalysis. 33–36 Atomically precise gold nanoclusters offer precise control over their geometric structure, electronic properties, and surface ligands, thus holding significant appeal as catalysts for electrochemical reactions due to their ultrasmall size and high surface-active sites.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrasmall sized MNCs are a class of materials that offer unique molecular-like properties, significant Stokes shift, high and tunable photoluminescence (PL), high photostability, and long lifetime making them promising materials for single-molecular studies. These luminescent NCs outperform organic dyes and quantum dots in terms of their excellent photostability and biocompatibility. Factors such as ligands, doping, number of atoms, and surface motifs play an important role in modifying the energy levels of MNCs to control the carrier relaxation dynamics. To facilitate easy characterization at the single molecule level, it is essential for MNCs to exhibit high luminescence at the ensemble as well as at single molecule levels. One strategy for tuning the luminescence property of MNCs is by doping the MNCs with other transition metals like Au, Ag, Cu, Pt, etc. Doping of monometallic nanoclusters can drastically enhance the luminescence, quantum yield, and photostability of MNC, which can be beneficial for practical applications like sensing, bioimaging, and catalysis. Bimetallic or alloy NCs have an edge over single-element MNCs as they have more degrees of freedom which can be manipulated to tune the optical properties. , It has been previously reported that doping Au element in Ag NCs is an effective way of tuning the optical properties of Ag NCs. Xia’s group has reported the influence of incorporating Ag atoms in rod-shaped Au 25 NCs for enhancing the photoluminescence properties by stabilization of HOMO and LUMO orbitals due to the replacement of Au atoms by Ag.…”
mentioning
confidence: 99%